PSYCHOLOGICAL AGE OF ADOLESCENTS: NORMAL OR DEVIATION - Khovrin А. N.; Khovrina, G. B. (Modern Psychology, 2019)
Problem’s urgency is based on the necessity to study students’ psychological features during the stage of transition from Elementary to Secondary school. On this stage of development the changes in attitude towards teacher and school education are natural. They depend on the change of eras, transition from childhood to adolescence, start of teen-age crisis and can be perceived as an indicator of changes in child’s development. This paper’s goal is to show the psychological features of students, who are entering Secondary school. The primary methods of our research were questionnaire survey, stating experiment and projective method. Research data shows significant difference between students’ psychological and chronological (passport) age. Psychological age of most students, who enter Secondary school, is primary school age and it impedes the process of education and interaction with teachers. Research data, presented in the paper may help teachers, parents and students understand the reasons of school problems and help children to adapt to the new system of social relations.